Preparation method of porous polyacrylonitrile fiber material, porous polyacrylonitrile fiber material and application
Porous polyacrylonitrile fiber materials are prepared by electrospinning and solution soaking, which solves the problems of difficult control of the preparation process in the prior art and vulnerable damage to the fiber structure, and realizes the preparation of materials with high porosity and good ionic conductivity, which is suitable for lithium battery separators.
Patent Information
- Application Number
- CN202510075199.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing preparation methods of porous polyacrylonitrile fiber materials are difficult to control during spinning. The removal process of pore-forming agents is complex and easily damaged the fiber structure, resulting in low ionic conductivity of the lithium battery separator and affecting performance.
By preparing the polyacrylonitrile spinning liquid and electrospinning, a polyacrylonitrile nanofiber membrane was obtained, which was then soaked in a mixed solution of N,N-dimethylformamide and deionized water. Through the interaction of the solution and polyacrylonitrile, the rearrangement and crystallization of the polymer macromolecular chains were initiated to form a porous morphology.
This method saves raw materials, has a simple pore-making process and good effect. The prepared porous polyacrylonitrile fiber material has high porosity, good electrolyte absorption and ionic conductivity. It is suitable for battery separators and improves ion transmission efficiency and thermal stability.
Smart Images

Figure CN119800609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous polypropylene fiber material preparation, and more specifically to a method for preparing a porous polyacrylonitrile fiber material and the porous polyacrylonitrile fiber material and its application. Background Art
[0002] Electrospinning is a special fiber manufacturing process that uses a polymer solution or melt to jet-spin fibers in a strong electric field. Electrospinning can be used to produce nonwoven nanofiber membranes with large surface area and interconnected porous structures, with high porosity, high liquid electrolyte absorption rate and ideal paths for ion migration, which can be used as battery separators.
[0003] Polyacrylonitrile is selected as the electrospinning material for lithium battery separators due to its high dielectric constant, good ionic conductivity, high liquid electrolyte absorption and excellent thermal stability. However, there is a strong polar organic group (-CN) on the side chain of polyacrylonitrile molecules, and there are strong interactions between polyacrylonitrile molecules. Therefore, only some solvents can evenly disperse the polymer molecules to form a homogeneous system of completely dissolved molecular dispersions.
[0004] Porous fibers have excellent loading and release capabilities due to their high specific surface area, high porosity and easy chemical modification, which makes them have important technical application prospects in the fields of energy storage and conversion, catalyst carriers, adsorption, separation and biomaterials. At present, the preparation of porous polyacrylonitrile nanofibers mainly depends on the addition of pore-forming agents and the phase separation process. Specifically, a pore-forming agent with different properties is added to the polyacrylonitrile matrix, and after spinning, different phase structures are formed in the fiber through the phase separation effect. Subsequently, the pore-forming agent is removed by thermal decomposition or solvent dissolution to obtain a porous polyacrylonitrile nanofiber. However, this method has to mix multiple substances during the spinning process, and the spinning conditions are changeable and difficult to control. In addition, when removing the pore-forming agent from the initial spinning fiber, the conditions are harsh and the process is long and complicated, which can easily damage the porous structure of the polyacrylonitrile fiber, resulting in low ionic conductivity, thereby affecting the performance of the lithium battery separator.
[0005] Therefore, how to provide a porous polyacrylonitrile fiber material with excellent performance is a technical problem that technical personnel in this field need to solve urgently. Summary of the invention
[0006] In view of this, the present invention proposes the following objectives:
[0007] One of the purposes of the present invention is to provide a method for preparing porous polyacrylonitrile fiber material.
[0008] A second object of the present invention is to provide a porous polyacrylonitrile fiber material.
[0009] A third object of the present invention is to provide a use of porous polyacrylonitrile fiber material.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] An embodiment of the present invention provides a method for preparing a porous polyacrylonitrile fiber material, which specifically comprises the following steps:
[0012] S1, preparing a polyacrylonitrile spinning solution, and performing electrospinning to prepare a polyacrylonitrile nanofiber membrane;
[0013] S2. Immerse the polyacrylonitrile nanofiber membrane prepared in S1 in a mixed solution of N,N-dimethylformamide and deionized water, take it out after immersion, and dry it to obtain a porous polyacrylonitrile fiber material.
[0014] Further, in S1, the process of preparing the polyacrylonitrile spinning solution is: dissolving polyacrylonitrile in N,N-dimethylformamide, stirring, and obtaining a clarified polyacrylonitrile spinning solution;
[0015] Furthermore, the mass ratio of the polyacrylonitrile to the N,N-dimethylformamide is (0.63-1.76):10;
[0016] Furthermore, the dissolving temperature is 80°C;
[0017] Furthermore, the stirring is performed at 120 r / min for 6-8 h;
[0018] Furthermore, the molecular weight of the polyacrylonitrile is 80,000-250,000 Da.
[0019] Further, in S1, the electrospinning process is: adding the polyacrylonitrile spinning solution into an electrospinning machine for electrospinning to obtain a polyacrylonitrile nanofiber membrane;
[0020] Furthermore, the spinning conditions are a temperature of 25-30° C. and a humidity of 20-35%.
[0021] Furthermore, during spinning, the working voltage was 15 kV, the distance between the spinning needle and the receiving roller was 25 cm, the flow rate was 0.8 mL / h, and the fixed speed of the receiving roller was 60 r / min;
[0022] Furthermore, the spinning time is 3h-4h.
[0023] Further, in S2, the mixed solution of N,N-dimethylformamide and deionized water is prepared by mixing deionized water and N,N-dimethylformamide in a mass ratio of 1:(6.5-10) and stirring;
[0024] Furthermore, the stirring is 120r / min for 25-35min.
[0025] Furthermore, in S2, the soaking time is 1-8 minutes.
[0026] Further, in S2, the drying is natural air drying in a fume hood;
[0027] Furthermore, the natural air-drying time is 24 hours.
[0028] A second aspect of the embodiments of the present invention is to provide a porous polyacrylonitrile fiber material, wherein the porous polyacrylonitrile fiber material is prepared by the method described above.
[0029] The third aspect of the embodiment of the present invention is to provide the use of the porous polyacrylonitrile fiber material, and the use includes any one of the following:
[0030] 1) Application in the preparation of battery separators;
[0031] 2) Application in improving thermal stability of battery separators;
[0032] 3) Application in improving the ionic conductivity of battery separators;
[0033] 4) Application in increasing the electrolyte absorption capacity of battery separators.
[0034] Through the above technical scheme, it can be known that the technical effect achieved by the present invention is: the present invention uses a small amount of polar and non-polar mixed solution to soak polyacrylonitrile spinning fibers to obtain porous polyacrylonitrile fiber materials, and the mixed solution of N,N-dimethylformamide and deionized water interacts with polyacrylonitrile to induce the rearrangement and crystallization of polymer macromolecular chains to form a porous morphology. The process of the present invention saves raw materials, the pore-making process is simple, and the pore-making effect is good and the efficiency is high. The prepared porous polyacrylonitrile fiber material has good porosity, electrolyte absorption and ion conductivity, can be used as a battery separator, improves ion transmission efficiency, has good thermal stability, and can improve the cycle capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0036] Attached Figure 1 This is an electron microscope image of the porous polyacrylonitrile fiber material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing a porous polyacrylonitrile fiber material comprises the following steps:
[0040] S1. Dissolve 1 g of polyacrylonitrile with a molecular weight of 150,000 in 9 g of N,N-dimethylformamide at 80° C. and stir at a stirring rate of 120 r / min for 7 h to obtain a clear polyacrylonitrile spinning solution;
[0041] S2, adding the polyacrylonitrile spinning solution obtained in step S1 into an electrospinning machine for electrospinning at a temperature of 25°C and a humidity of 30%, setting the working voltage to 15 kV, the distance between the spinning needle and the receiving roller to 25 cm, the flow rate to 0.8 mL / h, the fixed speed of the receiving roller to 60 r / min, spinning for 3 h, and obtaining a polyacrylonitrile nanofiber membrane;
[0042] S3, 3 g of deionized water and 28 g of N, N-dimethylformamide were mixed, and the mixture was stirred at a stirring rate of 120 r / min for 30 min to obtain a mixed solution of N, N-dimethylformamide and deionized water;
[0043] S4. Immerse the polyacrylonitrile nanofiber membrane in a mixed solution of N,N-dimethylformamide and deionized water, take it out after soaking for 3 minutes, and naturally air-dry it in a fume hood for 24 hours to obtain porous polyacrylonitrile fiber.
[0044] Example 2
[0045] A method for preparing a porous polyacrylonitrile fiber material comprises the following steps:
[0046] S1, 1 g of polyacrylonitrile with a molecular weight of 150,000 was dissolved in 9 g of N,N-dimethylformamide at 80°C and stirred at a stirring rate of 120 r / min for 7 h to obtain a clear polyacrylonitrile spinning solution;
[0047] S2, adding the polyacrylonitrile spinning solution obtained in step S1 into an electrospinning machine, performing electrospinning at a temperature of 25°C and a humidity of 30%, setting the working voltage to 15 kV, the distance between the spinning needle and the receiving roller to 25 cm, the flow rate to 0.8 mL / h, the fixed speed of the receiving roller to 60 r / min, spinning for 3 h, and obtaining a polyacrylonitrile nanofiber membrane;
[0048] S3, 3 g of deionized water and 27 g of N, N-dimethylformamide were mixed, and the mixture was stirred at a stirring rate of 120 r / min for 35 min to obtain a mixed solution of N, N-dimethylformamide and deionized water;
[0049] S4. Immerse the polyacrylonitrile nanofiber membrane in a mixed solution of N,N-dimethylformamide and deionized water, take it out after soaking for 3 minutes, and naturally air-dry it in a fume hood for 24 hours to obtain porous polyacrylonitrile fiber.
[0050] Example 3
[0051] A method for preparing a porous polyacrylonitrile fiber material comprises the following steps:
[0052] S1, dissolving 1 g of polyacrylonitrile with a molecular weight of 150,000 in 9 g of N,N-dimethylformamide at 80° C., stirring at a stirring rate of 120 r / min for 6 h, to obtain a clear polyacrylonitrile spinning solution;
[0053] S2, adding the polyacrylonitrile spinning solution obtained in step S1 into an electrospinning machine for electrospinning at a temperature of 25°C and a humidity of 30%, setting the working voltage to 15 kV, the distance between the spinning needle and the receiving roller to 25 cm, the flow rate to 0.8 mL / h, the fixed speed of the receiving roller to 60 r / min, spinning for 3 h, and obtaining a polyacrylonitrile nanofiber membrane;
[0054] S3, 3 g of deionized water and 26 g of N, N-dimethylformamide were mixed, and the mixture was stirred at a stirring rate of 120 r / min for 25 min to obtain a mixed solution of N, N-dimethylformamide and deionized water;
[0055] S4. Immerse the polyacrylonitrile nanofiber membrane in a mixed solution of N,N-dimethylformamide and deionized water, soak for 3 minutes, then take out and dry to obtain porous polyacrylonitrile fiber.
[0056] Comparative Example 1
[0057] A method for preparing a porous polyacrylonitrile fiber material comprises the following steps:
[0058] 1 g of polyacrylonitrile with a molecular weight of 150,000 was dissolved in 9 g of N,N-dimethylformamide at 80°C and stirred at a stirring rate of 120 r / min for 7 hours to obtain a clarified polyacrylonitrile spinning solution. The polyacrylonitrile spinning solution was added into an electrospinning machine for electrospinning under environmental conditions of a temperature of 25°C and a humidity of 30%. The working voltage was set to 15 kV, the distance between the spinning needle and the receiving roller was 25 cm, the flow rate was 0.8 mL / h, the fixed speed of the receiving roller was 60 r / min, and the spinning was carried out for 3 hours to obtain a polyacrylonitrile fiber material.
[0059] The difference between this comparative example and Example 1 is that the polyacrylonitrile nanofiber membrane is not immersed in a mixed solution of N,N-dimethylformamide and deionized water for treatment, but the polyacrylonitrile fiber material is directly obtained.
[0060] The polyacrylonitrile fiber materials prepared in Examples 1 to 3 and Comparative Example 1 were tested, and the test process was as follows:
[0061] 1. Electrolyte Absorption
[0062] Weigh a fiber material with a mass of M0, soak the fiber material in a lithium hexafluorophosphate electrolyte solution for 1 hour, then take it out, drain the excess electrolyte solution on the surface of the fiber material, weigh the fiber material again, record it as M1, and calculate the electrolyte absorption amount according to the following formula.
[0063] EU=(M1-M0) / M0×100%
[0064] The test results are shown in Table 1.
[0065] Table 1
[0066]
[0067] 2. Ionic conductivity
[0068] The cut fiber materials are soaked in lithium hexafluorophosphate electrolyte one by one, and the fully soaked fiber materials are placed on the diaphragm ion conductivity test equipment one by one. The AC amplitude is 1V, and the frequency range is 10kHz~1MHz. The equipment automatically injects liquid and tests to obtain the electrochemical impedance spectrum EIS curve. The intersection of the curve and the x-axis is Rs, and the n-layer diaphragm obtains the corresponding impedance value Rs(n). The single-layer diaphragm impedance R of the sample is calculated by linear fitting with the measured impedance values of 1 to 5 layers and the number of layers. Substitute the single-layer resistance into the formula to calculate the ionic conductivity:
[0069] Where: σ-ionic conductivity; d-diaphragm thickness; R-ionic resistance; S-effective area of test material.
[0070] The test results are shown in Table 2.
[0071] Table 2
[0072] Example 1 Example 2 Example 3 Comparative Example 1 Ionic conductivity (mS / cm) 4.71 4.24 4.11 3.29
[0073] 3. Thermal stability
[0074] Thermogravimetric analyzer and differential thermal analysis were used to evaluate the heat release and weight loss of the fiber material membrane under constant temperature heating in a N2 atmosphere and to test the thermal stability temperature.
[0075] The test results are shown in Table 3.
[0076] Table 3
[0077] Example 1 Example 2 Example 3 Comparative Example 1 Thermal stability temperature (℃) 290.3 290.7 291.2 294.5
[0078] 1. As can be seen from Table 1, the electrolyte absorption rate of Examples 1-3 is much higher than that of Comparative Example 1, and can absorb electrolyte solution 5 times the mass of the diaphragm itself, indicating that the porous polyacrylonitrile fiber material prepared in the present invention has a high electrolyte absorption capacity.
[0079] 2. As can be seen from Table 2, the ionic conductivity of Examples 1-3 is higher than that of Comparative Example 1, and the ionic conductivity can reach above 4.10 mS / cm, indicating that the porous polyacrylonitrile fiber material prepared by the present invention has good ionic conductivity.
[0080] 3. It can be seen from Table 3 that the thermal stability temperature of Examples 1-3 is above 290°C. The thermal stability temperature of the porous polyacrylonitrile fiber materials prepared in Examples 1-3 of the present invention used as battery separators is much higher than that of commercial battery separators on the market (Celgard2320, 130-165°C), indicating that the porous polyacrylonitrile fiber materials prepared in the present invention have excellent thermal stability.
[0081] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a porous polyacrylonitrile fiber material, characterized in that: The specific steps include: S1, preparing a polyacrylonitrile spinning solution, and performing electrospinning to prepare a polyacrylonitrile nanofiber membrane; S2. Immerse the polyacrylonitrile nanofiber membrane prepared in S1 in a mixed solution of N,N-dimethylformamide and deionized water, take it out after immersion, and dry it to obtain a porous polyacrylonitrile fiber material.
2. The method for preparing a porous polyacrylonitrile fiber material according to claim 1, characterized in that: In S1, the process of preparing the polyacrylonitrile spinning solution is: dissolving polyacrylonitrile in N,N-dimethylformamide, stirring, and obtaining a clarified polyacrylonitrile spinning solution; Preferably, the mass ratio of the polyacrylonitrile to the N,N-dimethylformamide is (0.63-1.76):10; Preferably, the dissolving temperature is 80°C; Preferably, the stirring is performed at 120 r / min for 6-8 h; Preferably, the molecular weight of the polyacrylonitrile is 80,000-250,000 Da.
3. The method for preparing a porous polyacrylonitrile fiber material according to claim 1, characterized in that: In S1, the electrospinning process is: adding the polyacrylonitrile spinning solution into an electrospinning machine for electrospinning to obtain a polyacrylonitrile nanofiber membrane; Preferably, the spinning conditions are a temperature of 25-30° C. and a humidity of 20-35%.
4. The method for preparing a porous polyacrylonitrile fiber material according to claim 3, characterized in that: During spinning, the working voltage was 15 kV, the distance between the spinning needle and the receiving roller was 25 cm, the flow rate was 0.8 mL / h, and the fixed speed of the receiving roller was 60 r / min; Preferably, the spinning time is 3-4 hours.
5. The method for preparing a porous polyacrylonitrile fiber material according to claim 1, characterized in that: In S2, the mixed solution of N,N-dimethylformamide and deionized water is prepared by mixing deionized water and N,N-dimethylformamide in a mass ratio of 1:(6.5-10) and stirring; Preferably, the stirring is at 120 r / min for 25-35 min.
6. The method for preparing a porous polyacrylonitrile fiber material according to claim 1, characterized in that: In S2, the soaking time is 1-8 minutes.
7. The method for preparing a porous polyacrylonitrile fiber material according to claim 1, characterized in that: In S2, the drying is natural air drying in a fume hood; Preferably, the natural air-drying time is 24 hours.
8. A porous polyacrylonitrile fiber material, characterized in that: The porous polyacrylonitrile fiber material is prepared by the method described in any one of claims 1-7.
9. The use of the porous polyacrylonitrile fiber material according to claim 8, characterized in that: The use includes any of the following: 1) Application in the preparation of battery separators; 2) Application in improving thermal stability of battery separators; 3) Application in improving the ionic conductivity of battery separators; 4) Application in increasing the electrolyte absorption capacity of battery separators.
Citation Information
Cited By
Preparation method of nanofiber non-woven fabric
CN121344875A